Using first year curriculum principles as an evidence-based approach to design and evaluate a first year seminar - Oosthuizen, L. L. (South African Journal of Higher Education, 2025)
This paper expands on and contributes to work in the field of transition in higher education, specific to the First Year Seminar (FYS). Although several studies have examined the efficacy of FYS programmes in supporting students’ transition into university, there is not much literature with a clear focus on the planning, execution, and evaluation of these programmes, particularly in the South African context. As such, the aim of this study is to use an evidence-based approach to design and evaluate an FYS. The research methodology draws on the constructive paradigm and makes use of a non-experimental, qualitative research design by employing a document analysis. Curriculum documents from the FYS at the University of the Free State (UFS) are analysed to answer the research question, “how can evidence-based FYS programmes be designed?” The study draws on Transition Pedagogy as the conceptual framework, specifically focusing on its First Year Curriculum Principles for design. Key findings indicate that the nature of the FYS at the UFS – a hybrid seminar integrated into the curriculum across all faculties – does meet the criteria for evaluating FYCPs. However, this investigation was also useful in determining ways to improve the design of this FYS to better support students’ transition into university. The implications of these findings are promising for the development of well-designed and evidence-based FYS programmes as core contributors to supporting first-year students’ transition into university.